Analysis of School Readiness in Developing School Digitalization at MA Al Hikmah Kajen - Mahfiroh, Sari; Mustika, Lutfia Richa Ayu; Rojaenah, Siti; Sulianto, Joko (Graduate Program Magister Manajemen Pendidikan, 2025)
This research aims to analyze the readiness of MA Al Hikmah Kajen in developing school digitalization, focusing on infrastructure, digital competence of teachers and students, principal's leadership, and obstacles. Digitalization is crucial for education quality, yet many institutions face implementation challenges. MA Al Hikmah, a madrasah in a pesantren environment, uses digital components like online admissions and virtual classrooms, but their daily application is limited by internal policies restricting student device use. Using a descriptive qualitative approach with interviews, observation, and documentation, the study found commendable infrastructure readiness. Teacher competence shows progress but is uneven, especially among senior educators. The principal's leadership positively supports digitalization, though more adaptive policy encouragement is needed. Key impediments are the student gadget ban and persistent digital literacy limitations among some teachers. The research recommends flexible policies, continuous digital training, and cultivating a digital ecosystem aligned with pesantren values.